Geolocalization of XIX Century Villages and Cities Mentioned in Geographical Dictionary of the Kingdom of Poland - Jaśkiewicz, Grzegorz Jan (Computer Science, 2013)
In this article it has been presented a method of rough estimation of geographical coordinates of villages and cities, which has been described in XIX century geographical encyclopedia entitled: "The Geographical dictionary of Polish Kingdom and other slavic countries". It has been described functioning of the algorithm for estimating location, the toolbox used to acquire and process necessary information, as well as context of this research.